"Collaborative Autoethnographic Writing as Communal Curative". Issue 4 (February 2023) - Alhayek, Katty; Alexander, Bryant Keith; Foster, Elissa; Ojeda, Carmen Hernandez; Mackie-Stephenson, Ayshia; Moreira, Claudio; Pelias, Ronald J.; Poulos, Christopher; Sutton, Timothy; Twishime, Porntip Israsena
This collaborative autoethnography reflects on how each author experienced COVID-19 and associated precarity. We explore the ways in which this experience relates to our identities (both particular and plural), and our positionalities in terms of privilege and marginality. As a collective of diverse collaborators, we confront dialectical questions of self and society. Our contributions reveal our advantage/disadvantage, mobility/immobility, and the borders and boundedness before/during/after COVID-19. We show the power of curative writing in collaborative autoethnography and how the sharing of our experiences of vulnerability represents an invitation to human connection.